Prognostic value of plasma levels of secretory type II phospholipase A2 in patients with unstable angina pectoris - Kugiyama, Kiyotaka; Ota, Yasutaka; Sugiyama, Seigo; Kawano, Hiroaki; Doi, Hideki; Soejima, Hirofumi; Miyamoto, Shinzo; Ogawa, Hisao; Takazoe, Keiji; Yasue, Hirofumi (The American journal of cardiology, 2000)
Plasma levels of secretory nonpancreatic type II phospholipase A2 (sPLA2) are increased in various chronic inflammatory diseases; this increase is correlated with disease severity. sPLA2 plays a possible role in atherogenesis and is highly expressed in atheromatous plaques. Thus, this study prospectively examined whether plasma levels of sPLA2 may have a prognostic value in patients with unstable angina, which is known to have inflammatory features. Plasma levels of sPLA2 were measured in 52 patients with unstable angina, in 107 patients with stable angina, and in 96 control subjects by radioimmunoassay. sPLA2 levels were significantly higher in patients with unstable angina than in those with stable angina and in control subjects. sPLA2 remained elevated after stabilization of disease. The levels were not increased in the blood in the coronary sinus. Kaplan-Meier analysis demonstrated that patients with unstable angina and with the higher sPLA2 levels had a significantly higher probability of developing clinical coronary events during a follow-up period of 2 years compared with those with the lower levels. In multivariate Cox hazard analysis, the higher levels of sPLA2 were a significant predictor of developing coronary events in patients with unstable angina, independent of other risk factors, including C-reactive protein levels, an established inflammatory predictor. In conclusion, the increase in circulating levels of sPLA2 predicts clinical coronary events independently of other risk factors in patients with unstable angina. sPLA2 levels were persistently elevated but the elevated levels may not be derived from coronary circulation.